Curve fitting using logarithmic function for sea bed logging data - Daud, H. (American Scientific Publishers, 2016)
The aim of this research work is to conduct curve fitting using mathematical equations that relate location of the hydrocarbon (HC) at different depths to different frequencies. COMSOL MultiPhysics software was used to generate models of the seabed logging technique which consists of air, sea water, and sediment and HC layer. Seabed Logging (SBL) is a technique to find the resistive layers under seabed by transmitting low frequency of EM waves through sea water and sediment. As HC is known to have high resistivity which is about 30-500 Î©m, EM waves will be guided and reflected back and detected by the receiver that are placed on the seafloor. In SBL, low frequency is used to obtain greater wavelength which allows EM waves to penetrate at longer distance and each frequency used has different skin depth. The frequencies used in this project were 0.5 Hz, 0.25 Hz, 0.125 Hz and 0.0625 Hz and the depths of the HC were varied from 1000 m to 3000 m with increment of 250 m. Data generated from COMSOL software was extracted for the set up with and without HC and trend lines using logarithmic functions were developed and R2 were calculated for each equation and curve. The calculated R2 was compared between data with HC to no HC at each depth and it was found that the calculated R2 values were very well fitted for deeper HC depth. This indicates that as depth of HC is higher, it is difficult to distinguish data with and without HC presence; and perhaps a new technique can be explored. Â© Copyright 2016 American Scientific Publishers All rights reserved.